2013
DOI: 10.1021/jp311044a
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion Studies of Dihydroxybenzene Isomers in Water–Alcohol Systems

Abstract: Nuclear magnetic resonance diffusion studies can be used to identify different compounds in a mixture. However, because the diffusion coefficient is primarily dependent on the effective hydrodynamic radius, it is particularly difficult to resolve compounds with similar size and structure, such as isomers, on the basis of diffusion. Differential solution interactions between species in certain solutions can afford possibilities for separation. In the present study, the self-diffusion of the three isomers of dih… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 65 publications
0
25
0
Order By: Relevance
“…Similar results were observed for two other primary alcohols, but not for ethylene glycol. These results suggest that a carefully chosen co-solute could support matrix-assisted DOSY experiments, with an additional degree of separation possible 88 . A recent related development is the use of nanoparticles in detection of dissolved ions.…”
Section: Other Systemsmentioning
confidence: 82%
“…Similar results were observed for two other primary alcohols, but not for ethylene glycol. These results suggest that a carefully chosen co-solute could support matrix-assisted DOSY experiments, with an additional degree of separation possible 88 . A recent related development is the use of nanoparticles in detection of dissolved ions.…”
Section: Other Systemsmentioning
confidence: 82%
“…Another type of mixed matrix is that of a mixed solvent. It has previously been shown that ethanol/water mixtures change the relative diffusion coefficients of C, R, and H. [8] Here we investigated the use of ethanol and some common NMR solvents, methanol-d 4 and DMSO-d 6 , in aqueous solutions for resolution of C, R, and H (Table 3). For the mixed-solvents, D 2 O-methanol-d 4 and D 2 O-DMSO-d 6 , no advantage was seen at either of the proportions studied (17 and 92% v/v).…”
Section: Discussionmentioning
confidence: 99%
“…The method is sometimes referred to as chromatographic DOSY, particularly when using a chromatographic stationary phase as the matrix . A change in matrix can be something as simple as a change of solvent, or a change to a mixed solvent, altering the effective hydrodynamic radii of the species of interest . More commonly, the matrix is changed by adding a large species as a co‐solute to modulate the diffusion coefficients of the species that interact with it.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations